A nitrogen-phosphorus hybrid reaction type mesoporous silicon flame retardant and its preparation method and application
By using nitrogen-phosphorus hybridization-reactive mesoporous silicon flame retardant in glass fiber reinforced polyamide, the problems of low flame retardant grade of the material during combustion and poor compatibility of the expanded flame retardant are solved, and more efficient flame retardant performance and improved mechanical properties are achieved.
Patent Information
- Application Number
- CN202310170106.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-27
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2043-02-27
AI Technical Summary
Glass fiber reinforced polyamide engineering plastics are prone to 'wick effect' when burning, resulting in low flame retardant grades, limiting their application in electrical, transportation and other fields. The compatibility and dispersion of existing expansion flame retardants in polymer bodies are poor, resulting in low flame retardant efficiency.
A nitrogen-phosphorus hybridization reaction mesoporous silicon flame retardant is used. This flame retardant is chemically bonded to the polyamide molecular chain through the nitrogen, phosphorus and silicon ternary flame retardant groups, and uses the porous structure of mesoporous silicon and the hydroxyl active groups to improve compatibility and dispersion with the polymer.
The flame retardant and droplet resistance of glass fiber reinforced polyamide is significantly improved, the amount of flame retardant is added, the mechanical properties of the material are improved, and the 'wick effect' is effectively suppressed.
Smart Images

Figure CN116285002B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of flame retardants, and specifically relates to a nitrogen-phosphorus hybridization reaction type mesoporous silicon flame retardant and a preparation method and application thereof. Background Art
[0002] Polyamide engineering plastics have the advantages of high strength, good temperature resistance, excellent electrical insulation, oil resistance and wear resistance. They are widely used in the fields of electronics, mechanics, automobiles, chemical engineering, etc., and are one of the largest-volume engineering plastics in the world. The use of glass fiber to reinforce polyamide can greatly improve its strength and heat deformation temperature, which is an effective way to manufacture high-strength and heat-resistant polyamide. However, it will produce a "candle wick effect" when burning, which will reduce its flame retardant grade and limit its application in the fields of electricity and transportation. Therefore, the flame retardancy of glass fiber reinforced polyamide has always been a hot topic in the field of polymer flame retardancy.
[0003] At present, the flame retardants used for flame retardant modification of glass fiber reinforced polyamide are mainly phosphorus and nitrogen. The disadvantages are that the addition amount is large (generally 15%wt~35%wt) and the mechanical properties of the polymer body are deteriorated. Intumescent flame retardant (IFR) is a new type of flame retardant developed on the basis of traditional flame retardants. It is usually composed of three structural units: acid source (P=O), carbon source (CC, Ar) and gas source (NH2, N=C). Compared with traditional flame retardants, IFR has the advantages of high flame retardant efficiency, environmental friendliness, and halogen-free. However, it also has problems such as poor compatibility with the polymer body, low dispersion, poor carbonization effect, and hydrolysis resistance. It still has an important impact on the mechanical properties of the body material such as tensile strength and impact strength. In order to further improve the flame retardant efficiency of intumescent flame retardants, researchers combined IFR with silicon-based flame retardants, connected flame retardant groups with siloxanes through organic-inorganic hybridization, and took advantage of the stable Si-O-Si bond structure, high temperature resistance, and good hydrothermal stability to prepare new flame retardants with high efficiency, low toxicity, anti-drip, easy carbonization, and smoke suppression. Among them, mesoporous silica SBA-15 has attracted more and more attention as a synergist of flame retardants. Mesoporous silica SBA-15 has a uniform pore structure, a large specific surface area and high porosity, good thermal stability and hydrothermal stability, and can maintain the stability of the skeleton during high-temperature combustion. Its pore size can accommodate the molecular chain of the polymer, and the surface is rich in active groups such as hydroxyl groups, which are suitable for modification. Functional compounds can also be hybridized or adsorbed in the skeleton and pores. Based on the above characteristics, mesoporous silica SBA-15 has been studied as a synergist in the flame retardant field of polyethylene, polypropylene, polycarbonate, epoxy resin, polystyrene, polylactic acid and other polymers. By adding a small amount, it can inhibit combustion and smoke, improve water resistance and mechanical properties.
[0004] However, the effect of using mesoporous silica SBA-15 alone as a synergist is limited, as shown by the fact that the amount of intumescent flame retardant IFR added is still large (10%wt~25%wt), and the compatibility with the polymer body has not been improved. IFR, mesoporous silica SBA-15 and the polymer body material are in phase with each other, and the flame retardant and synergist cannot be evenly dispersed in the polymer body, which greatly reduces the flame retardant efficiency, and IFR is easy to precipitate or dissolve. Therefore, glass fiber reinforced polyamide materials are still unable to use intumescent flame retardants for higher flame retardancy requirements (for example: UL94 V-0 grade). Summary of the invention
[0005] One of the purposes of the present invention is to provide a nitrogen-phosphorus hybrid reaction type mesoporous silica flame retardant in view of the problems existing in the flame retardancy of existing glass fiber reinforced polyamide engineering plastics. The flame retardant does not contain halogen, and its porous structure and large pore size can accommodate polyamide molecular chains. The carboxyl functional groups of the flame retardant can be chemically bonded with the polyamide molecular chains. The silicon skeleton of the porous material has high hydrothermal stability and solvent resistance. The abundant hydroxyl groups on the surface of the mesoporous silica can be combined with the hydroxyl groups on the surface of the glass fiber through hydrogen bonds, so that the flame retardant can be highly dispersed in the glass fiber reinforced polyamide engineering plastics, which can not only make it have excellent flame retardant properties and anti-melting droplet properties, but also can significantly reduce the amount of flame retardant added, thereby improving the mechanical properties of the flame retardant polyamide engineering plastics.
[0006] A nitrogen-phosphorus hybrid reaction type mesoporous silica flame retardant, the structural formula of the flame retardant is shown in Formula 1:
[0007]
[0008] Among them, SBA-15-φ is a mesoporous molecular sieve, and its mass fraction in the flame retardant is 10% to 20%, and the pore size of the micropores inside the mesoporous molecular sieve silica is 10 to 30 nm; R1-PPTR-R2 is a homologue of 4,4'-((3,9-dioxido-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane-3,9-diyl)bis(aza nediyl))dibenzoic acid (abbreviated as PPTR) (when a=0 and b=0, it is PPTR; when a and / or b=1, it is a homologue of PPTR), and its mass fraction in the flame retardant is 80% to 90%.
[0009] The second object of the present invention is to provide a method for preparing the above-mentioned nitrogen-phosphorus hybridization reaction type mesoporous silica flame retardant, comprising the following specific steps:
[0010] (1) dissolving a polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123) in deionized water, adding tetraethyl silicate (TEOS) and hydrochloric acid, stirring vigorously for 24 to 48 hours, placing the mixture in a polytetrafluoroethylene bottle for crystallization for 24 to 48 hours, filtering, washing with water, and drying, and calcining at 520 to 580° C. for 5 to 8 hours to remove TEOS, and then filtering, washing with water, and drying to obtain a white powdery SBA-15 mesoporous molecular sieve; wherein the molar ratio of TEOS, P123, hydrochloric acid, and deionized water is 1:(0.1 to 0.5):(5 to 15):(130 to 150);
[0011] Preferably, the temperature when adding tetraethyl silicate (TEOS) and hydrochloric acid is 35-40°C;
[0012] (2) Pentaerythritol and phosphorus oxychloride are mixed in a molar ratio of 1:3, heated to 60-90° C. under nitrogen protection and stirred, then heated to 100-110° C. for reflux reaction, unreacted phosphorus oxychloride is removed by vacuum distillation, and dried to constant weight to obtain a white powdery intermediate product 3,9-dichloro-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane 3,9-dioxide (abbreviated as: DCDP), the structural formula of which is shown in Formula 2:
[0013]
[0014] Preferably, the stirring time is 80 to 120 minutes;
[0015] Preferably, the reflux reaction time is 10 to 12 hours;
[0016] (3) mixing the compound represented by Formula 3-1 with DCDP in a molar ratio of 2:1 to 2.6:1, adding a solvent and a catalyst, heating to reflux under nitrogen protection, filtering, washing, and drying to obtain a compound represented by Formula 3;
[0017]
[0018] In Formula 3-1 and Formula 3, R1 and R2 are methylene, a=0 or 1, b=0 or 1;
[0019] Preferably, the solvent is one of ethyl acetate or glacial acetic acid, and the added amount is 3 to 5 times the amount of p-aminobenzoic acid or its homologues;
[0020] Preferably, the catalyst is triethylamine;
[0021] (4) mixing the compound shown in Formula 3 with SBA-15 mesoporous molecular sieve in a mass ratio of 90:10 to 80:20, adding a solvent and a catalyst 4-dimethylaminopyridine; adding ethylene glycol ethyl ether in an amount of 2 to 3 times the total mass of the reactants as a solvent, heating and reacting the mixture for 6 to 24 hours, filtering, washing and drying to obtain a nitrogen-phosphorus hybrid reaction-type mesoporous silica flame retardant as shown in Formula 1;
[0022] Preferably, the solvent is ethylene glycol ethyl ether, and the added amount is 2 to 3 times the total mass of the compound represented by Formula 3 and the SBA-15 mesoporous molecular sieve.
[0023] The third object of the present invention is to provide a flame-retardant glass fiber reinforced polyamide engineering plastic, which contains the nitrogen-phosphorus hybridization reaction type mesoporous silica flame retardant provided by the present invention, with a mass fraction of 10% to 15%; the rest is glass fiber reinforced polyamide engineering plastic, wherein the mass fraction of glass fiber is 20% to 30% of the total mass, and the rest is polyamide resin. The flame-retardant glass fiber reinforced polyamide engineering plastic is prepared by fully mixing the nitrogen-phosphorus hybridization reaction type mesoporous silica flame retardant with glass fiber reinforced polyamide engineering plastic slices, and then melt-blending, extruding and pelletizing them through a twin-screw extruder.
[0024] Compared with the prior art, the present invention has the following advantages:
[0025] 1. The nitrogen-phosphorus hybrid reaction-type mesoporous silicon flame retardant provided by the present invention contains nitrogen, phosphorus, and silicon ternary flame retardant groups, wherein the nitrogen element can be converted into nitrogen to dilute oxygen in the gas phase, the phosphorus element can be converted into free radicals, oxides or phosphates, which respectively prevent the spread of flames and isolate flames in the gas phase and solid phase, and the silicon element can be converted into silicon dioxide to isolate flames in the solid phase. Compared with the prior art using nitrogen and phosphorus binary flame retardant groups, the flame retardant provided by the present invention has better flame retardant effect;
[0026] 2. The SBA-15 mesoporous molecular sieve in the nitrogen-phosphorus hybrid reaction-type mesoporous silica flame retardant provided by the present invention has a relatively large pore size (10nm≤pore size≤30nm), and the polyamide molecular chain can enter the molecular sieve pore and combine with the molecular chain outside the pore to form a network structure, thereby enhancing the interaction force between the polyamide body and the molecular sieve interface and improving the compatibility of the flame retardant and the polyamide body. Compared with the prior art, the amount of the flame retardant provided by the present invention added to the polyamide is significantly reduced (the mass fraction of the best embodiment is 10%), and the mechanical properties of the flame-retardant polyamide product are significantly improved;
[0027] 3. The nitrogen-phosphorus hybrid reaction-type mesoporous silica flame retardant provided by the present invention has a carboxyl reactive group, which can undergo a polycondensation reaction with a polyamide molecular chain with an amino reactive group to form a strong chemical bond, thereby substantially improving the compatibility of the flame retardant with polyamide, thereby avoiding the precipitation phenomenon that often occurs during the melt processing or solvent immersion process of the flame retardant. Compared with the prior art, the flame retardant provided by the present invention is used in a smaller amount in polyamide and has better flame retardant properties;
[0028] 4. The surface of the SBA-15 mesoporous molecular sieve in the nitrogen-phosphorus hybrid reaction-type mesoporous silica flame retardant provided by the present invention contains abundant hydroxyl groups, which can be combined with the hydroxyl groups on the surface of the glass fiber in the form of hydrogen bonds and cover the surface of the glass fiber to reduce its "candle wick effect". Compared with the prior art, the flame retardant prepared by the present invention can effectively improve the flame retardant properties of glass fiber reinforced polyamide;
[0029] 5. The pore wall of the SBA-15 mesoporous molecular sieve in the nitrogen-phosphorus hybrid reaction-type mesoporous silica flame retardant provided by the present invention has excellent thermal insulation, hydrolysis resistance and solvent resistance, and the nitrogen and phosphorus flame retardant elements are firmly combined with the SBA-15 mesoporous molecular sieve and the polyamide main chain through chemical bonds. Compared with the prior art, the flame-retardant polyamide product prepared by the present invention has significantly improved heat resistance, water resistance and solvent resistance, and improved mechanical properties;
[0030] 6. The preparation method provided by the present invention is simple, mature and easy to industrialize. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 The figure is a flow chart of the method of the present invention. DETAILED DESCRIPTION
[0032] The following examples are given to further illustrate the present invention. It is necessary to point out that the following examples cannot be understood as limiting the scope of protection of the present invention. If a person skilled in the art makes some non-essential improvements and adjustments to the present invention based on the above content of the present invention, it still belongs to the scope of protection of the present invention.
[0033] The flame retardant properties of the flame retardant glass fiber reinforced polyamide engineering plastic samples used in the following examples are measured by the UL94 vertical combustion method; the tensile strength is measured using GB / T 1447-2005 "Test method for tensile properties of fiber reinforced plastics"; and the notched impact strength is measured using the GB / T 1843-2008 "Determination of cantilever beam impact strength of plastics" method.
[0034] Example 1: Preparation of mesoporous silica flame retardant PPTR / SBA-15-30
[0035] (1) Add 324g (18mol) of deionized water and 188g (1.8mol) of concentrated hydrochloric acid to a 1L round-bottom flask and mix them thoroughly. Add 20g (0.06mol) of P123 preheated at 40°C to the hydrochloric acid solution, heat and stir in a water bath at 40°C for 4h until completely dissolved, then slowly drop 25.06g (0.12mol) of TEOS and stir vigorously at 40°C for 48h. After the reaction is completed, transfer the mixed solution to a hydrothermal reactor lined with polytetrafluoroethylene and place it in a 100°C oven for crystallization for 48h. Finally, filter the obtained product, wash it to pH 4-5 and dry it. The obtained white powder is calcined in a high-temperature furnace at 580°C for 8h (heating rate 1K / min) to obtain 24.3g of SBA-15 mesoporous molecular sieve. The pore size is 29.6nm as determined by nitrogen adsorption-desorption experiment, i.e. SBA-15-30.
[0036] (2) 13.615 g (0.1 mol) of pentaerythritol and 45.999 g (0.3 mol) of phosphorus oxychloride were added to a 100 mL three-necked round-bottom flask, connected with a thermometer and a reflux condenser, heated to 60° C. and stirred for 80 min under nitrogen protection, then heated to 105° C. and refluxed for 10 h. Unreacted phosphorus oxychloride was removed by vacuum distillation, and dried to constant weight to obtain 28.784 g of a white powdery intermediate product, 3,9-dichloro-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane 3,9-dioxide (abbreviated as DCDP). 1 HNMR (400MHz, DMSO-d6) δ4.23ppm, 31 P (122MHz, Chloroform-d) δ-3.09ppm, the structural formula is as follows:
[0037]
[0038] (3) 28.784 g (0.097 mol) of DCDP and 26.605 g (0.194 mol) of p-aminobenzoic acid were added to a 250 mL four-necked round-bottom flask, and 79.815 g of ethyl acetate and 0.294 g (0.003 mol) of triethylamine were added. One port of the four-necked flask was connected to a reflux condenser, one port was connected to a tail gas absorption device, and one port was inserted into a nitrogen tube. Nitrogen was continuously introduced and a slight positive pressure was maintained in the reactor. Mechanical stirring was started and the mixture was slowly heated to reflux. The reaction was maintained until no hydrogen chloride gas was released. The obtained white suspension was filtered, washed with ethyl acetate and deionized water in turn, and dried to obtain 47.279 g of a white product (abbreviated as: PPTR). 1 H NMR (400 MHz, DMSO-d6) δ 4.37-4.43, 7.12-7.87 ppm, the structural formula is as follows:
[0039]
[0040] (4) Take 24g (0.048mol) of PPTR, 2.677g of SBA-15-30, and 0.176g (0.0014mol) of 4-dimethylaminopyridine and add them into a 150mL three-necked round-bottom flask, add 53.354g of ethylene glycol ethyl ether, connect a thermometer, a reflux condenser, and a water separator, start stirring, slowly heat to reflux, react for 6h, filter the reaction product, wash the filter cake with ethylene glycol ethyl ether and deionized water, and dry at 120°C to obtain 24.668g of a white fine powder product, i.e., a nitrogen-phosphorus hybrid reaction-type mesoporous silica flame retardant PPTR / SBA-15-30. Thermogravimetric analysis experiments confirmed that the mass fraction of PPTR was 88.7%.
[0041] Example 2: Preparation of mesoporous silica flame retardant CH2-PPTR / SBA-15-20
[0042] (1) In a 1 L round-bottom flask, add 378 g (21 mol) of deionized water and 156.3 g (1.5 mol) of concentrated hydrochloric acid, respectively, and mix thoroughly. Then, add 10 g (0.03 mol) of P123 preheated at 40°C dropwise to the hydrochloric acid solution, heat in a water bath at 40°C and stir for 4 h until completely dissolved. Then, slowly add 31.33 g (0.15 mol) of TEOS dropwise, and stir vigorously at 40°C for 36 h. After the reaction, the mixed solution was transferred to a hydrothermal reactor lined with polytetrafluoroethylene, placed in a 100°C oven for crystallization for 36 hours, and finally the obtained product was filtered, washed to pH 4-5 and dried. The obtained white powder was calcined in a high-temperature furnace at 550°C for 6 hours (heating rate 1K / min) to obtain 30.74 g of SBA-15 mesoporous molecular sieve. The pore size was 19.4 nm as determined by nitrogen adsorption-desorption experiment, namely SBA-15-20.
[0043] (2) According to Example 1(2), 28.784 g of DCDP was prepared;
[0044] (3) 28.784 g (0.097 mol) of DCDP and 30.791 g (0.204 mol) of 4-(aminomethyl)benzoic acid were added to a 250 mL four-necked round-bottom flask, and 123 g of glacial acetic acid and 0.825 g (0.008 mol) of triethylamine were added. One port of the four-necked flask was connected to a reflux condenser, one port was connected to a tail gas absorption device, and one port was inserted into a nitrogen tube. Nitrogen was continuously introduced and a slight positive pressure was maintained in the reactor. Mechanical stirring was started and the mixture was slowly heated to reflux. The reaction was maintained until no hydrogen chloride gas was released. The obtained white suspension was filtered, washed with glacial acetic acid and deionized water in turn, and dried to obtain 48.561 g of a white product (abbreviated as: CH2-PPTR). 1HNMR (400MHz, DMSO-d6) δ 4.41-4.43, 7.09-7.81ppm, the structural formula is as follows:
[0045]
[0046] (4) Take 25.265g (0.048mol) of CH2-PPTR, 4.459g of SBA-15-20, and 0.232g (0.0019mol) of 4-dimethylaminopyridine and add them into a 250mL three-necked round-bottom flask, add 89.172g of ethylene glycol ethyl ether, connect a thermometer, a reflux condenser, and a water separator, start stirring, slowly heat to reflux, react for 7h, filter the reaction product, wash the filter cake with ethylene glycol ethyl ether and deionized water, and dry at 120°C to obtain 29.478g of a white fine powder product, which is a nitrogen-phosphorus hybrid reaction-type mesoporous silica flame retardant CH2-PPTR / SBA-15-20. Thermogravimetric analysis experiments confirmed that the mass fraction of PPTR-CH2 was 83.7%.
[0047] Example 3: Preparation of mesoporous silica flame retardant PPTR-CH2 / SBA-15-15
[0048] (1) In a 1 L round-bottom flask, add 486 g (27 mol) of deionized water and 156.4 g (1.5 mol) of concentrated hydrochloric acid, respectively, and mix thoroughly. Then, add 10 g (0.03 mol) of P123 preheated at 40°C dropwise to the hydrochloric acid solution, heat in a water bath at 40°C with stirring for 4 h until completely dissolved. Then, slowly add 41.67 g (0.2 mol) of TEOS dropwise, and stir vigorously at 40°C for 36 h. After the reaction, the mixed solution was transferred to a hydrothermal reactor lined with polytetrafluoroethylene, placed in a 100°C oven for crystallization for 36 hours, and finally the obtained product was filtered, washed to pH 4-5 and dried. The obtained white powder was calcined in a high-temperature furnace at 550°C for 6 hours (heating rate 1K / min) to obtain 40.86g of SBA-15 mesoporous molecular sieve. The pore size was 15.4nm as detected by nitrogen adsorption-desorption experiment, that is, SBA-15-15.
[0049] (2) According to Example 1(2), 28.784 g of DCDP was prepared;
[0050] (3) 28.784 g (0.097 mol) of DCDP and 30.791 g (0.204 mol) of p-aminophenylacetic acid were added to a 250 mL four-necked round-bottom flask, and 123 g of glacial acetic acid and 0.825 g (0.008 mol) of triethylamine were added. One port of the four-necked flask was connected to a reflux condenser, one port was connected to a tail gas absorption device, and one port was inserted into a nitrogen tube. Nitrogen was continuously introduced and a slight positive pressure was maintained in the reactor. Mechanical stirring was started and the mixture was slowly heated to reflux. The reaction was maintained until no hydrogen chloride gas was released. The obtained white suspension was filtered, washed with glacial acetic acid and deionized water in turn, and dried to obtain 47.852 g of a white product (abbreviated as: PPTR-CH2). 1 H NMR (400 MHz, DMSO-d6) δ 4.12, 4.38-4.42, 7.11-7.86 ppm, the structural formula is as follows:
[0051]
[0052] (4) Take 25.265g (0.048mol) of PPTR-CH2, 4.459g of SBA-15-15, and 0.232g (0.0019mol) of 4-dimethylaminopyridine and add them into a 250mL three-necked round-bottom flask, add 89.172g of ethylene glycol ethyl ether, connect a thermometer, a reflux condenser, and a water separator, start stirring, slowly heat to reflux, react for 7h, filter the reaction product, wash the filter cake with ethylene glycol ethyl ether and deionized water, and dry at 120°C to obtain 29.527g of a white fine powder product, which is a nitrogen-phosphorus hybrid reaction-type mesoporous silica flame retardant PPTR-CH2 / SBA-15-15. Thermogravimetric analysis experiments confirmed that the mass fraction of PPTR-CH2 was 82.9%.
[0053] Example 4: Preparation of mesoporous silica flame retardant CH2-PPTR-CH2 / SBA-15-10
[0054] (1) Add 702g (39mol) of deionized water and 156.7g (1.5mol) of concentrated hydrochloric acid to a 1L round-bottom flask and mix them thoroughly. Add 10g (0.03mol) of P123 preheated at 35°C to the hydrochloric acid solution, heat and stir in a water bath at 35°C for 4h until completely dissolved, then slowly add 62.66g (0.3mol) of TEOS and stir vigorously at 35°C for 24h. After the reaction is completed, transfer the mixed solution to a hydrothermal reactor lined with polytetrafluoroethylene and place it in a 100°C oven for crystallization for 24h. Finally, filter the obtained product, wash it to pH 4-5 and dry it. The obtained white powder is calcined in a high-temperature furnace at 520°C for 5h (heating rate 1K / min) to obtain 62.13g of SBA-15 mesoporous molecular sieve. The pore size is 9.7nm as determined by nitrogen adsorption-desorption experiment, i.e. SBA-15-10.
[0055] (2) According to Example 1(2), 28.784 g of DCDP was prepared;
[0056] (3) 28.784 g (0.097 mol) of DCDP and 41.653 g (0.252 mol) of 4-aminomethylphenylacetic acid were added to a 500 mL four-necked round-bottom flask, and 208.265 g of glacial acetic acid and 1.315 g (0.013 mol) of triethylamine were added. One port of the four-necked flask was connected to a reflux condenser, one port was connected to a tail gas absorption device, and one port was inserted into a nitrogen tube. Nitrogen was continuously introduced and a slight positive pressure was maintained in the reactor. Mechanical stirring was started and the mixture was slowly heated to reflux. The reaction was maintained until no hydrogen chloride gas was released. The obtained white suspension was filtered, washed with glacial acetic acid and deionized water in turn, and dried to obtain 52.739 g of a white product (abbreviated as: CH2-PPTR-CH2). 1HNMR (400 MHz, DMSO-d6) δ 4.12, 4.41-4.43, 7.11-7.86 ppm. The structural formula is as follows:
[0057]
[0058] (4) Take 26.612g (0.048mol) of CH2-PPTR-CH2, 6.653g of SBA-15-10, and 0.293g (0.0024mol) of 4-dimethylaminopyridine and add them into a 250mL three-necked round-bottom flask, add 166.325g of ethylene glycol ethyl ether, connect a thermometer, a reflux condenser, and a water separator, start stirring, slowly heat to reflux, react for 24h, filter the reaction product, wash the filter cake with ethylene glycol ethyl ether and deionized water, and dry at 120°C to obtain 33.136g of a white fine powder product, which is a nitrogen-phosphorus hybrid reaction-type mesoporous silica flame retardant CH2-PPTR-CH2 / SBA-15-10. Thermogravimetric analysis experiments confirmed that the mass fraction of CH2-PPTR was 78.5%.
[0059] Example 5: Preparation of PPTR / SBA-15-30 flame retardant 30% glass fiber reinforced polyamide 66 (PA66GF30)
[0060] Take 30g of the nitrogen-phosphorus hybrid reaction-type mesoporous silica flame retardant PPTR / SBA-15-30 prepared in Example 1 and 2100g of polyamide 66 resin slices, stir them thoroughly to make the flame retardant evenly dispersed in the polyamide 66 resin slices; melt-blended and extruded the polyamide resin slices mixed with the flame retardant through a 35-type twin-screw extruder, and 900g of long glass fiber was added from the side feed port and extruded together with the resin slices; the temperature of each section of the twin-screw extruder was 225°C in zone I, 235°C in zone II, 245°C in zone III, 245°C in zone IV, and 235°C in zone V. 5℃, zone VI 215℃, screw speed 60r / min; the extruded strips were water-cooled, pelletized by a rotary pelletizer, and dried to obtain flame-retardant glass fiber reinforced polyamide 66 resin slices, wherein the mass fraction of nitrogen-phosphorus hybrid reactive mesoporous silica flame retardant PPTR / SBA-15-30 was 10%; the flame-retardant slices were prepared into standard vertical combustion (0.8mm) specimens, tensile specimens and notched impact specimens by an injection molding machine, the injection molding temperature was 240℃, the mold temperature was 110℃, and the combustion test and mechanical property test were carried out respectively. The results are shown in Table 1.
[0061] Examples 6 to 11: Flame-retardant glass fiber reinforced polyamide engineering plastic samples with different addition amounts were prepared in the same manner as in Example 5. The test results are summarized in Table 1.
[0062] Comparative Examples 1 and 2: Take PPTR and SBA-15-30 prepared in Example 1 (3) and Example 1 (1) respectively, and prepare glass fiber reinforced polyamide 66 (PA66GF30) engineering plastic samples according to the same method as Example 5, and compare them with Example 5, in order to examine the flame retardant effect and mechanical properties of PPTR and SBA-15 when used alone, so as to verify the flame retardant properties of the nitrogen-phosphorus hybrid reaction type mesoporous silica flame retardant provided by the present invention.
[0063] Table 1 Flame retardant effect and mechanical properties of engineering plastics of Examples 5-11 and Comparative Examples 1-2
[0064]
[0065]
Claims
1. A nitrogen-phosphorus hybrid reaction type mesoporous silica flame retardant, characterized in that: The structural formula of the flame retardant is shown in Formula 1: Among them, SBA-15 is a mesoporous molecular sieve, and its mass fraction in the nitrogen-phosphorus hybrid reaction type mesoporous silicon flame retardant is 10% to 20%, and the pore size of the micropores inside the mesoporous molecular sieve is 10 to 30 nm; R1 and R2 are methylene, a=0 or 1, b=0 or 1.
2. The method for preparing the nitrogen-phosphorus hybrid reaction type mesoporous silica flame retardant according to claim 1, characterized in that: The preparation method comprises the following steps: (1) dissolving a polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer P123 in deionized water, adding ethyl silicate TEOS and hydrochloric acid, stirring for 24 to 48 hours, placing in a polytetrafluoroethylene bottle for crystallization for 24 to 48 hours, filtering, washing with water, and drying, and calcining at 520 to 580° C. for 5 to 8 hours to remove ethyl silicate TEOS, and then filtering, washing with water, and drying to obtain an SBA-15 mesoporous molecular sieve; wherein the molar ratio of TEOS, P123, hydrochloric acid, and deionized water is 1:(0.1 to 0.5):(5 to 15):(130 to 150); (2) pentaerythritol and phosphorus oxychloride are mixed in a molar ratio of 1:3, heated to 60-90° C. under nitrogen protection, stirred, then heated to 100-110° C. for reflux reaction, and dried to constant weight after reduced pressure distillation to obtain an intermediate product DCDP with a structural formula shown in Formula 2; (3) Mixing the compound represented by Formula 3-1 and DCDP in a molar ratio of (2 to 2.6):1, adding a solvent and a catalyst, heating to reflux under nitrogen protection, filtering, washing, and drying to obtain a compound represented by Formula 3; In Formula 3-1 and Formula 3, R1 and R2 are methylene, a=0 or 1, b=0 or 1; (4) The compound shown in Formula 3 is mixed with SBA-15 mesoporous molecular sieve in a mass ratio of (90:10) to (80:20), a solvent and a catalyst are added, and the mixture is reacted under heating conditions for 6 to 24 hours. After filtering, washing, and drying, a nitrogen-phosphorus hybrid reaction-type mesoporous silica flame retardant is obtained.
3. The preparation method according to claim 2, characterized in that: The stirring time of step (2) is 80 to 120 minutes.
4. The preparation method according to claim 2, characterized in that: The reflux reaction time of step (2) is 10 to 12 hours.
5. The preparation method according to claim 2, characterized in that: The solvent in step (3) is one of ethyl acetate or glacial acetic acid, and the added amount is 3 to 5 times the mass of the compound represented by formula 3-1.
6. The preparation method according to claim 2, characterized in that: The catalyst in step (3) is triethylamine.
7. The preparation method according to claim 2, characterized in that: The solvent in step (4) is ethylene glycol ethyl ether, and the added amount is 2 to 3 times the total mass of the compound represented by formula 3 and the SBA-15 mesoporous molecular sieve.
8. The preparation method according to claim 2, characterized in that: The catalyst in step (4) is 4-dimethylaminopyridine.
9. A flame retardant glass fiber reinforced polyamide engineering plastic, characterized in that: The engineering plastic comprises the nitrogen-phosphorus hybridization reaction type mesoporous silica flame retardant according to claim 1 and glass fiber reinforced polyamide engineering plastic; wherein the mass fraction of the nitrogen-phosphorus hybridization reaction type mesoporous silica flame retardant is 10% to 15%.
Citation Information
Patent Citations
Flame-retardant composite material with DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) modified nano mesoporous molecular sieve
CN102675895A
Reaction type nitrogen and phosphorus modified graphene modified polyurethane flame-retardant material and preparation method thereof
CN111533876A